Set Your Agricultural Publications Free in the HathiTrust Repository. Issue 1 (2nd January 2017) - McGeachin, Robert B.
ABSTRACT: The HathiTrust repository contains agricultural Experiment Station and Extension Service publications from all 50 of the United States. But to freely display the post-1923 documents, HathiTrust requires a Permission Agreement form giving them a nonexclusive permission to distribute from the copyright holder. Agriculture librarians are encouraged to obtain signed Permission Agreement forms for the agricultural publications in HathiTrust from their state. Once Permission Agreement forms are obtained from your local copyright holding administrators, submit them to HathiTrust at (feedback@issues.hathitrust.org).